Association of oxidative balance score with all-cause and cardiovascular mortality among patients with cardio-renal-metabolic disease - Lin, Yucui; Wang, Yunxia; Liu, Cailing; Ye, Danjie; Huang, Ziran; Ou, Yangbin; Gu, Wenjun; Ma, Jianhong (Frontiers in Nutrition, 2025)
BackgroundCardio-renal-metabolic (CRM) conditions are increasingly recognized as a major public health challenge, with oxidative stress playing a pivotal role in poor prognosis. The oxidative balance score (OBS) is used to assess the body’s oxidative stress status, but its link to all-cause and cardiovascular mortality in CRM patients remains unclear.MethodsWe used data from participants (≥ 20 years old) in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. The patients were divided into four groups based on OBS using the weighted quartiles method. The relationship between OBS and both all-cause and cardiovascular mortality in CRM patients was assessed using multivariable Cox regression and restricted cubic spline (RCS) models. The differences in cumulative survival between groups were examined using Kaplan–Meier analysis and log-rank tests. Sensitivity analysis and subgroup analysis were also performed.ResultsDuring a median follow-up of 7.9 years, there were 3,838 (25.2%) and 1,412 (8.9%) patients who died from all-cause and cardiovascular mortality, respectively. After adjusting for potential confounders, elevated OBS level was negatively related to the risk of all-cause mortality [Q2, Q3, Q4: adjusted hazard ratio (aHR) (95 confidence interval (CI%)) = 0.85 (0.75–0.96), 0.87 (0.77–0.98), 0.74 (0.62–0.88), respectively; P for trend<0.001]. Moreover, Higher OBS quartiles were linked to a decreased risk of cardiovascular mortality, while no significant reduction was observed in the lower quartiles [model 3: Q2, Q3, Q4: aHR (95CI%) = 0.96(0.77–1.19), 0.78 (0.63–0.97), 0.70 (0.53–0.93), respectively; P for trend = 0.003]. Kaplan–Meier survival analysis also indicated that patients in the highest quartile of OBS had the lowest risk of both all-cause mortality and cardiovascular mortality (log-rank test p < 0.001). Furthermore, restricted cubic spline analyses revealed an inverse relationship between OBS levels and the risk of both all-cause and cardiovascular death. The sensitivity analyses confirmed the stability of our findings.ConclusionElevated levels of OBS were negatively related to the risk of all-cause and cardiovascular mortality among CRM patients, which may offer valuable information on the role of oxidative stress status for risk stratification of mortality in CRM patients.